Investigation and comparison of lineouts during the 2013 the rugby championship and six-nations competition - Franken, L.; van Vuuren, H.; Kraak, W.; Vaz, L. (International Journal of Performance Analysis in Sport, 2017)
A successful lineout is a key component of team success in international rugby and yet there is limited published research on this topic. Lineouts are seen as a great attacking modality, which occur to restart play after the ball exits the field of play. The aim of the study was to investigate and compare the lineouts during the 2013 The Rugby Championship and Six-Nations Competition. Twenty-seven matches of the 2013 international season were analysed using EncodePro video analysis software. Outcome measures were presented as the mean ± s. Cohen`s d effect sizes were calculated, using the difference in means over the pooled standard deviation, to characterise the differences between the two tournaments. Results indicated the largest difference in formation was the average 5- man lineouts in TRC vs. SNC per match (9.58 ± 3.90 vs. 6.93 ± 3.01) and 7-man (10.42 ± 4.36 vs. 11.60 ± 3.31). The exiting from lineouts yielded some differences in TRC and SNC per match with regard to passing (12.75 ± 4.35 vs. 6.87 ± 2.33) and mauls (5.33 ± 5.53 vs. 6.80 ± 2.81). The study indicated that most lineouts occurred in Zone B with binding formation followed by pass being the most utilised formats. Lineouts should be adapted according to the area of field in which it occurs to ensure greater try-scoring opportunities.